2010
DOI: 10.1002/ptr.3018
|View full text |Cite
|
Sign up to set email alerts
|

Lucidone, a novel melanin inhibitor from the fruit of Lindera erythrocarpa Makino

Abstract: The effects of lucidone on tyrosinase and antimelanogenic activity were investigated. Initially, we found that lucidone strongly inhibits the activity of mushroom tyrosinase. The effects of lucidone on tyrosinase were further examined in alpha-MSH-induced B16 melanoma cells. Lucidone significantly inhibits tyrosinase activity and leads to decreased melanin content in cultured B16 melanoma cells. Lucidone also attenuates the expression of tyrosinase and MITF (Microphthalmia-associated Transcription Factor) prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…The lucidone derivatives, such as methyllinderone and methyllucidone, also exhibited anti-inflammation activity and anti-farnesyl protein transferase (16,17). Recent in vitro and animal model studies have demonstrated that lucidone exerts anti-inflammatory activity with significant suppression of iNOS and COX-2 production (16,18) and antimelanogenic activity (19). In the present study, we characterize the anti-HCV activity of lucidone and evaluate its possible mechanism of action against HCV replication.…”
mentioning
confidence: 92%
“…The lucidone derivatives, such as methyllinderone and methyllucidone, also exhibited anti-inflammation activity and anti-farnesyl protein transferase (16,17). Recent in vitro and animal model studies have demonstrated that lucidone exerts anti-inflammatory activity with significant suppression of iNOS and COX-2 production (16,18) and antimelanogenic activity (19). In the present study, we characterize the anti-HCV activity of lucidone and evaluate its possible mechanism of action against HCV replication.…”
mentioning
confidence: 92%
“…The synthesis of novel CPDs is often devoted to modification of natural CPDs resulting in structure-activity relationship (SAR) studies and subsequent discoveries of novel bioactives with applicability in chemical technologies, biotechnology and biomedicine fields. Among well studied CPD representatives are lucidone and linderone with anti-inflammatory activities [2][3][4][5], cytostatic compound TX-1123 [6], involutone constituent of fungi Paxillus involutus [7][8][9], madindolines [10][11][12][13] and nostotrebin 6 [14][15][16] attributed to enzyme inhibitory effects. The novel synthetic approaches are primarily focused on total synthesis of above-mentioned CPDs and also on strategies for development of structurally simplified CPDs with biological, especially antibacterial and antifungal activities.…”
Section: Introductionmentioning
confidence: 99%
“…Smalley et al 12) reported that the levels of ERK1/2 phosphorylation in B16 cells were enhanced by α-MSH (10 nM) treatment. In contrast, according to the paper by Kumar et al,18) the level of phosphorylation was not affected in the presence of α-MSH (100 nM). In our experiment, phosphorylation was suppressed time-dependently at 6 and 12 h, regardless of the presence or absence of α-MSH (Fig.…”
Section: Effect Of Noni Extracts On Melanogenesis In α-Mshstimulated mentioning
confidence: 73%